Measuring electronic word-of-mouth effectiveness : developing and applying the eWOM trust scale - Weitzl, Wolfgang (Springer Gabler, 2017)
Wolfgang Weitzl introduces a novel perspective for measuring consumer trust in eWOM by applying a rigid scale development process. In doing so, the research aims to set new methodical standards for developing reliable, valid and practicable research instruments. Most importantly, however, the research offers valuable insights into the nature and role of consumer-initiated vs. marketer-initiated online communication in an intercultural context by conducting a series of qualitative and quantitative surveys using samples from three countries. Contents Interdisciplinary Literature Review on Trust Conceptualizing and Identifying the Role of eWOM Trust Developing the eWOM Trust Scale by Testing its Dimensionality, Reliability, Validity and Generalizability Applying the eWOM Trust Scale for Segmenting Online Information Recipients Target Groups Researchers and students of online marketing and consumer research, as well as communications Market and consumer researchers as well as consultants The Author Wolfgang Weitzl, PhD is assistant professor of marketing communication at the University of Vienna and research associate at the WU Vienna University of Economics and Business. His research and teaching focus is on brand management, market communication and consumer engagement. Here, his emphasis is on B2C and C2C online interactions including negative word-of-mouth, complaining, online service recoveries and integrated communication in the digital era.
Keywords: Word-of-mouth advertising.; Internet marketing.; elektronické knihy; electronic books